2010
DOI: 10.1177/1948550610385872
|View full text |Cite
|
Sign up to set email alerts
|

Deliberate Practice Spells Success

Abstract: The expert performance framework distinguishes between deliberate practice and less effective practice activities. The current longitudinal study is the first to use this framework to understand how children improve in an academic skill. Specifically, the authors examined the effectiveness and subjective experience of three preparation activities widely recommended to improve spelling skill. Deliberate practice, operationally defined as studying and memorizing words while alone, better predicted performance in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
147
0
5

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 448 publications
(189 citation statements)
references
References 21 publications
(29 reference statements)
6
147
0
5
Order By: Relevance
“…The first indicator was a teacher nomination, for which teachers were asked to consider logical/analytic thinking, abstract thinking, mathematical thinking, scientific/technical thinking, language skills, learning ability, power of deduction/combination, broad knowledge, and special knowledge of a domain in the process of identifying gifted children (Heller, 2004). Despite clear instructions, teachers usually base their nomination of a gifted child on the assumption of innate giftedness by identifying those children who are able to excel with limited support (Lohman, 2005b;Subotnik et al, 2011) or those who are able to have a high level of achievement due to their hard work (Duckworth, Kirby, Tsukayama, Berstein, & Ericsson, 2010;Gagné, 2010). This indicator was therefore assumed to provide an indirect indication of giftedness.…”
Section: Criteria For Identifying Giftednessmentioning
confidence: 99%
“…The first indicator was a teacher nomination, for which teachers were asked to consider logical/analytic thinking, abstract thinking, mathematical thinking, scientific/technical thinking, language skills, learning ability, power of deduction/combination, broad knowledge, and special knowledge of a domain in the process of identifying gifted children (Heller, 2004). Despite clear instructions, teachers usually base their nomination of a gifted child on the assumption of innate giftedness by identifying those children who are able to excel with limited support (Lohman, 2005b;Subotnik et al, 2011) or those who are able to have a high level of achievement due to their hard work (Duckworth, Kirby, Tsukayama, Berstein, & Ericsson, 2010;Gagné, 2010). This indicator was therefore assumed to provide an indirect indication of giftedness.…”
Section: Criteria For Identifying Giftednessmentioning
confidence: 99%
“…Duckworth and Quinn (2009) explored the ability of grit to differentiate individuals' retention in specific programs, through multiple studies with varying populations. Grittier adults were more likely to pursue further education (Duckworth & Quinn, 2009), less likely to withdraw from military training programs (Duckworth & Quinn, 2009;Eskreis-Winkler, Shulman, Beal, & Duckworth, 2014), more likely to keep their jobs (Eskreis-Winkler et al, 2014), more likely to stay married (Eskreis-Winkler et al, 2014), and grittier spellers engaged more time in deliberate practice compared to less gritty individuals (Duckworth, Kirby, Tsukayama, Berstein, & Ericsson, 2011). Therefore, it can be suggested that potential retention and engagement in various disciplines can be explained by an individual's level of grit.…”
mentioning
confidence: 99%
“…Although researchers have identified the potential for grit to predict retention within specific programs (Duckworth & Quinn, 2009;Duckworth et al, 2011;Eskreis-Winkler et al, 2014), there remains limited understanding of the how grit may influence aspects of performance. Duckworth and colleagues (2011) have attempted to understand this link through an expertise approach examining performance at a national junior spelling competition.…”
mentioning
confidence: 99%
“…Psychosocial strength or grit is at the centre of eminent levels of achievement and needs to be strategically delivered to support students through key transitions in their talent development (Duckworth, et al, 2010). This helps lead to self-efficacy, selfdetermination and self-actualisation which are goals for all students.…”
Section: Social Emotional Needs In Transitionmentioning
confidence: 99%